Effect Of Foam Rolling Followed By Cold Water Immersion On Muscle Damage And Delayed Onset Muscle Soreness In Youth Soccer Players - Hedroug , Nadir (sports creativity, 2025)
The study aimed to know the effect of foam rolling followed by cold water immersion recovery on muscle damage and delayed onset muscle soreness(DOMS) in youth soccer players after high intensity effort, the study included 20 players of ESS team U19 category from the Algerian championship, the players were randomly divided into two groups 10 players per group (experimental and control ), the experimental group used foam rolling followed by cold water immersion us recovery protocol, while the control group had no recovery protocol. firstly the players simulated yoyo test L1 the blood sample had been taken, before,1h,24h after to know the concentration of (CK) and the rate of recovery, also we used visual analogy scale(VAS) before, immediately, after 48h to know the effects of the method on muscle pain and delayed onset muscle soreness(DOMS). The results of this study showed that foam rolling followed by cold-water immersion recovery could be used as a useful way to decrease muscle damage and muscle soreness. Keywords: foam roller(FR)- cold water immersion(CWI)- muscle damage- muscle soreness(DOMS)